HUBUNGAN FREKUENSI MEROKOK, LAMA MEROKOK DAN JENIS ROKOK TERHADAP PEWARNAAN GIGI - Oshi Wulandari Sulistyaningrum (FKU 12 UMY, 2012)
Tooth discoloration is a prime aesthetics complaint of smoker to a dentist. Smoking frequency, smoking habit duration and kind of cigarette consume are guessed as the influence factors of tooth discoloration. Based on the compotition there are cigarette and cigar. Cigar have a clove addition on it. This research using Tooth Discoloration Index by Shaw and Murray as a measurer. It examine with a mouth mirror and plaid fabric. It examine 31 male smoker. Subject is asked to complete a smoking habi